Erythema nodosum and the risk of tuberculosis in a high incidence setting. Issue 1 (31st January 2016) - Bjorn-Mortensen, Karen; Ladefoged, Karin; Simonsen, Jacob; Michelsen, Sascha W.; Sørensen, Hans Christian F.; Koch, Anders; Lillebaek, Troels; Andersen, Aase Bengaard; Soborg, Bolette
Abstract : Objective: This study estimates the erythema nodosum (EN) incidence in a tuberculosis (TB) endemic setting and evaluates the likelihood of a subsequent TB diagnosis among individuals with Mycobacterium tuberculosis infection (MTI) with or without EN. Design: We estimated EN incidence rates (IRs) in East Greenland in 2010–2011 and conducted a cohort study following all individuals who tested positive for MTI from 1 January 2010 until 31 December 2012. A personal identifier allowed individual follow-up in the mandatory TB register. MTI was defined by a positive interferon-gamma release assay. TB incidence rate ratios (IRRs) among participants with or without EN were estimated with the Cox proportional hazard model. Results: We identified 38 EN cases corresponding to an IR of 500/100, 000 inhabitants/year. All cases were among individuals with MTI. The EN IR was 11.79 (95% CI 5.73–24.27) times higher for BCG-unvaccinated compared with BCG-vaccinated individuals. The TB IRR was 25 (95% CI 11–60) within 1 month of EN compared to individuals without EN. Conclusion: This study documents a high EN incidence in a TB endemic region. EN occurred only in individuals with MTI, and predominantly among BCG-unvaccinated individuals. EN was significantly associated with a TB diagnosis within 1 month of diagnosis.